Metabolic syndrome and discrepancy between actual and self-identified good weight: Aerobics Center Longitudinal Study. (March 2015) - Wirth, Michael D.; Blake, Christine E.; Hébert, James R.; Sui, Xuemei; Blair, Steven N.
Highlights: Weight discrepancy was defined as measured minus self-reported goal weight. Weight discrepancy was associated with smoking and physical inactivity at baseline. Chronic high weight discrepancy was associated with metabolic syndrome risk. Interventions targeting weight discrepancy may help lower metabolic syndrome risk. Abstract: This study examined whether the discrepancy between measured and self-identified good weight (weight discrepancy) predicts metabolic syndrome (MetSyn). This study included 6, 413 participants enrolled in the Aerobics Center Longitudinal Study (mean follow-up: 4.8 ± 3.8 years). Weight discrepancy was defined as measured weight minus self-identified good weight. MetSyn was defined using standard definitions. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for incident MetSyn, by weight discrepancy category, were estimated using Cox proportional hazards regression. The multivariable-adjusted HR for MetSyn was 3.48 (95% CI = 2.48–4.86) for those who maintained higher weight discrepancy over time compared to individuals with lower weight discrepancy. Additional adjustment for body mass index did not change this interpretation (HR = 3.44; 95% CI = 2.46–4.82). Weight discrepancy may be a useful screening characteristic and target for future interventions to further reduce the risk of chronic weight-related disorders, included MetSyn.